2023
DOI: 10.3390/ijerph20021652
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Correlation between Dental Occlusion, Postural Stability and Selected Gait Parameters in Adults?

Abstract: Background: There is still an ongoing debate about the role of the craniomandibular system, including occlusal conditions, on postural stability. This study aims to assess the role of antero-posterior malocclusion on postural control and plantar pressure distribution during standing and walking. Methods: 90 healthy volunteers (aged 19 to 35) were qualified for the study. The subjects were assigned to three groups, depending on the occlusion type. Each group (Angle Class I, II and III) consisted of 30 people. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Another crucial aspect of our study was analyzing center of pressure (CoP) dynamics [4] and the potential association with skeletal class. Although no significant differences were found in anteroposterior CoP displacement among skeletal classes, similar to previous findings [13,48,49], our results suggest that jaw biomechanics could influence body weight distribution, subsequently affecting posture and balance. Significant differences in maximum heel forces were found with a large effect size relative to non-pathological cases, with existing studies linking lower limb differences to plantar pressures [50].…”
Section: Discussionsupporting
confidence: 89%
“…Another crucial aspect of our study was analyzing center of pressure (CoP) dynamics [4] and the potential association with skeletal class. Although no significant differences were found in anteroposterior CoP displacement among skeletal classes, similar to previous findings [13,48,49], our results suggest that jaw biomechanics could influence body weight distribution, subsequently affecting posture and balance. Significant differences in maximum heel forces were found with a large effect size relative to non-pathological cases, with existing studies linking lower limb differences to plantar pressures [50].…”
Section: Discussionsupporting
confidence: 89%
“…This allows action to be taken in advance, minimizing the risk of undesirable events developing during treatment. [ 18 ] A comprehensive approach involves developing an individualized risk management plan for each patient, taking into account their unique characteristics and abnormalities. This ensures that the treatment plan is personalized and as safe as possible, taking into account all potential risks.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in asymptomatic participants and with vision, Sakaguchi et al [ 8 ] reported a longer length in RP than in ICP, whereas Amaricai et al [ 13 ] reported a smaller sway area in RP than in ICP. Other studies, such as Nowak et al [ 28 ], focused only on the influence of severe malocclusion in ICP. They reported an increased instability (increased mean length and sway area) in case of malocclusion (Class II and III) compared to normocclusion (Class I), but no inter-group difference in RQ.…”
Section: Discussionmentioning
confidence: 99%
“…These dependent variables were calculated for each of the 10 tested conditions (5 mandibular positions, with and without vision) and for the first and last 25.6 s time periods. A 5th variable, the Romberg Quotient (100*area without vision/area with vision) was also computed [ 28 ]. The Romberg Quotient was used to determine individuals for whom visual information can be considered preponderant (>1) or not (≤1) in static postural control in standing position.…”
Section: Methodsmentioning
confidence: 99%